Study on the Surgical Techniques in Maxillary Sinus Floor Elevation - Liu Sixuan (BIO Web of Conferences)
Patients with dental caries and periodontal problems may experience tooth loss, leading to alveolar bone resorption, maxillary sinus hyperpneumatization, and ultimately affecting implant implantation due to insufficient bone height. Maxillary sinus elevation surgery increases bone height by lifting the sinus membrane, solving the problem of insufficient bone height during dental implant surgery in the posterior region. This review summarizes the surgical methods, indications, and contraindications of maxillary sinus elevation surgery, and summarizes the advantages and disadvantages of various methods currently used in clinical practice. This review aims to provide practical guidance for the future development of maxillary sinus elevation surgery through a detailed review of current literature.